2003
DOI: 10.1007/s11605-003-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Cystic pancreatic neoplasms: Enucleate or resect?

Abstract: Asymptomatic cystic pancreatic neoplasms are being detected by abdominal imaging with increasing frequency. Enucleation of small cystic neoplasms can be performed without recurrence but has been associated with a higher incidence of pancreatic fistula. Thus the procedure has been modified to include intraoperative ultrasound imaging and closure of the pancreatic defect. This analysis was performed to determine whether these modifications have improved operative outcome. Thirty patients with mucinous cystic neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 23 publications
7
64
1
1
Order By: Relevance
“…Sixty percent of cases in this group were cystic neoplasm. Though in many series of cystic neoplasm of pancreas spleen was not preserved, some series attempted it with favorable outcome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Sixty percent of cases in this group were cystic neoplasm. Though in many series of cystic neoplasm of pancreas spleen was not preserved, some series attempted it with favorable outcome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that enucleation might be safe and effective alternative for patients with benign MCAs. MCAs are also mentioned and cited in Kiely's et al study [90]. Similarly to the SCAs, short-term results of the surgical treatment depend on the pancreatic resection type.…”
Section: Management In Mucinous Cystadenoma and Cystadenocarcinomamentioning
confidence: 94%
“…Simple cystic enucleation (for peripherally located SCAs), in order to preserve pancreatic parenchyma, has been described in the literature. Kiely et al [90] compared enucleation and resection (proximal and distal pancreatectomy) results in 30 patients with mucinous cystic neoplasms (n=16), serous cystadenomas (n=10), and cystic islet cell tumors (n=4). Authors reported significantly shorter operative time in the enucleation group (199 vs. 298 minutes) and significantly reduced blood loss in the enucleation group (114 vs. 450 ml) compared to the resection group.…”
Section: Management In Serous Cystadenoma and Cystadenocarcinomamentioning
confidence: 99%
“…Distal pancreatectomy with splenic vessel preservation may lead to remnant pancreatic tissue on the splenic vessel, and therefore it is not advised in patients with malignant disease. However, in chronic pancreatitis or benign diseases, the number of cases with spleen preservation is high (33,34). Spleen preservation was shown to be associated with reductions of postoperative infection and length of hospital stay.…”
Section: Surgical Techniquesmentioning
confidence: 99%